2016
DOI: 10.1186/s12958-016-0163-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nerve growth factor on sperm quality in asthenozoosprmic men during cryopreservation

Abstract: BackgroundAlthough routinely used in assisted reproductive technology, human sperm cryopreservation is not an entirely successful procedure. This study determined the effect of nerve growth factor (NGF) supplementation of cryopreservation medium on post-thaw viability, motility, intracellular nitric oxide (NO) concentration, and DNA fragmentation of human spermatozoa in asthenozoospermic men.MethodsSemen samples were collected from 25 asthenozoosprmic men and divided into the following groups (n = 5/group): fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 43 publications
1
17
0
1
Order By: Relevance
“…However, cryopreservation of semen is usually associated with diminished motility, viability, and DNA damage of the sperm (McLaughlin et al 1992;Kalthur et al 2008). In recent years, the recovery results of frozen sperm have improved with the development of cryopreservation technology (Li et al 2010;Valcarce et al 2013;Saeednia et al 2016)). However, most studies have focused on clinical pregnancies resulting from frozen donor sperm (Chen et al 2012;Zarek et al 2014;Kop et al 2015;Guan et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, cryopreservation of semen is usually associated with diminished motility, viability, and DNA damage of the sperm (McLaughlin et al 1992;Kalthur et al 2008). In recent years, the recovery results of frozen sperm have improved with the development of cryopreservation technology (Li et al 2010;Valcarce et al 2013;Saeednia et al 2016)). However, most studies have focused on clinical pregnancies resulting from frozen donor sperm (Chen et al 2012;Zarek et al 2014;Kop et al 2015;Guan et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The first indication of a measured NGF content in human exposed that the level of NGF protein in seminal plasma gained from oligoasthenozoospermic and asthenozoospermic was lower in comparison to fertile semen although these differences were not statistically significant . Parallel to the study above, a work is done by Saeednia et al in 2016 showed that the seminal NGF concentration was significantly higher (Pvalue <0.05) in normozoospermic compared with asthenozoospermic men (Saeednia et al, 2016). The decrease in serum and seminal NGF levels in asthenozoospermic and oligoasthenozoospermic men may have a substantial part in the aetiology of sperm dysfunction.…”
Section: Figure 2: the Correlation Between Cat And Gsh In Patients Wimentioning
confidence: 65%
“…Other additives that are reported to protect sperm against damage include antioxidants which primarily work to neutralize ROS generated during the cryopreservation process and thus improve post-thaw sperm function. The commonly employed antioxidants include vitamin E, vitamin C, catalase, l-carnitine, biotin, butylated hydroxytoluene, taurine, hyaluronic acid, resveratrol, honey, and nerve growth factor [49][50][51][52][53]. Antifreeze proteins and glycoproteins are another group of cryoprotective supplements that can be employed in sperm freezing that help to maintain the plasma membrane integrity by stabilizing the phospholipids and unsaturated fatty acids [50].…”
Section: Solution To Cryoinjuriesmentioning
confidence: 99%